AN APPLICATION OF SANGHVATTHU PRINCIPLES (4) IN PUBLIC WEFARE WORK OF SANGHA IN SURAT THANI PROVINCE - Phrakhrupaiyatkunawut; Phrakhrusiridhammapirat; Wongnasri, Punnapong (Journal of MCU Nakhondhat, 2023)
The objectives of this research article were 1) to study about the rule of the public welfare work, 2) to study about Sangahavatthu 4 involved in the public welfare work, and 3) to apply the principle of Sangahavatthu 4 to the public welfare work for Buddhist clergy in Suratthani. The qualitative research was conducted for this study. The 20 key informants consisted of Buddhist ecclesiastical official monk and Head of government / Scholar for management. The in-depth interview was conducted as the research tool. The data were analyzed by context based and the descriptive method was used for the presentation. The research findings were emerged as the followings: 1) The rule of public welfare consisted of 6 entries which were considered in (1) Monitoring and supporting goodness maintenance, (2) Religious studies, (3) Educational welfare, (4) Buddhism propagation, (5) Public assistance, and (6) Public welfare, 2) The principles of Sangahavatthu 4 were (1) Dana (liberality) : giving; generosity; charity, (2) Piyavaca (kind speech) : using kindly speech to convince any people, (3) Atthacariya (beneficial actions) : doing well and rendering services, and (4) Samanattata (impartiality) : behaving oneself even and equal treatment properly in all circumstances and producing admirableness and truthfulness as a true friend. 3) There were 5 aspects for applying the principle of Sangahavatthu 4 to the public welfare work for Buddhist clergy in Suratthani. The 5 aspects of service are the followings: (1) Conducting services, (2) Conducting any services for public welfare work, (3) Doing favors and participation in public work, (4) Performing actions that are useful and helpful to other people, and (5) Facilitating the building and location for instance: charity hall, crematorium, morgue, etc. Wat (Buddhist temple) becomes the center of national arts and cultures.